Correlation of Objective Audiometric and Caloric Function in Ménière's Disease. (May 2017) - McMullen, Kyle P.; Lin, Chen; Harris, Michael S.; Adunka, Oliver F.
Objective: Ménière's disease affects the vestibular and audiologic systems; however, little is known about the relationship between audiometric and caloric function with increasing duration of disease. We employed a novel methodology to understand the longitudinal correlation between audiometric and caloric function in Ménière's patients. Study Design: Case series with chart review. Setting: Neuro-otologic tertiary care practice. Subjects and Methods: Charts of 19 patients with unilateral Ménière's disease, as classified by the 1995 American Academy of Otolaryngology—Head and Neck Foundation criteria, were examined. We included patients with ≥2 videonystagmograms and audiograms. We excluded those with bilateral Ménière's, prior audiovestibular destruction, or symptoms suggesting concomitant vestibular pathology. Spearman's rank correlation of audiometric status (pure tone average [PTA], low PTA, and word recognition score [WRS]) and vestibular function (bithermal calorics) was performed. The study was Institutional Review Board approved (protocol 2015H0266). Results: A total of 112 audiograms and 42 videonystagmographies were performed. There was a decline in affected ear hearing PTA and WRS with duration of disease ( r = 0.602, P < .001, and r = −0.573, P < .001, respectively). Similarly, there was a decline in vestibular function with increasing duration of disease ( r = 0.709, P < .001). There were moderate correlations between vestibular weakness and PTA, low PTA, and WRS ( r = 0.464, P = .002; r = 0.498, P = .001; and r = −0.518, P = .001, respectively). Conclusions: There is a correlation between decline in objective hearing and horizontal semicircular canal function with time. As expected, this correlation is not 1:1, indicating differential involvement of both systems. Understanding this relationship may assist in counseling patients with regard to prognosis, natural history, and therapeutic interventions.